Savage peace hope and fear in America, 1919 - Hagedorn, Ann (Simon & Schuster, 2007)
The surprising story of America in the year 1919--democracy under stress. In the aftermath of an unprecedented world war and a flu pandemic, Americans were full of hope for the benefits of peace. But instead, the fear of terrorism filled their days. Bolshevism was the new menace, and the federal government, utilizing a vast network of domestic spies, began to watch anyone deemed suspicious. A young lawyer named J. Edgar Hoover headed a brand-new intelligence division (later to become the FBI). Bombs exploded on the doorstep of the attorney general's home in Washington, D.C. Wartime legislation to curb criticism of the government was extended and even strengthened. Labor strife was a daily occurrence. Decorated African-American soldiers, returning home to claim the democracy for which they had risked their lives, were badly disappointed. Weaving together the stories of a panoramic cast of characters, from Albert Einstein to Helen Keller, author Hagedorn illuminates America at a pivotal moment.